BANGUNAN KOLONIAL BELANDA YANG MASIH BERDIRI DI JAKARTA SEBAGAI OBJEK WISATA BUDAYA - Heny Ratnaningtyas; Nurbaeti Nurbaeti; Fetty Asmaniati (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
The purpose of this study was to determine the utilization of Dutch colonial buildings inJakarta which were used as cultural tourism. This study uses a type of field research using aqualitative approach. To find out the history of the city of Jakarta and the architecture of theDutch colonial buildings, the authors took data from previous research books and journals.As for the state of the Dutch Colonial building which is still standing in Jakarta, the authorconducted interviews with 5 (five) informants, namely tourists, the public, researchers,lecturers and the tourism of fice. The results of the study show that 9 (nine) Dutch colonialbuildings in the city of Jakarta are in very good condition because they are well managed andcared for by the DKI Jakarta government and historical evidence that Jakarta used to be theresid ence of the Dutch who had visited the city of Batavia and carried out activities.colonialism in Batavia which made the activities of the City of Jakarta now modern frombuilding architecture, social and new technology. For the DKI Jakarta government, it i shoped that the Dutch Colonial buildings will always be managed and cared for properly, sothat the existence of these buildings can maintain their historical value. For the people of DKI Jakarta, this Dutch Colonial building can be used as a cultural tourism object as a historicallesson for the next young generation who can know the history of the city, nation and country.